2008
DOI: 10.1093/hmg/ddn090
|View full text |Cite
|
Sign up to set email alerts
|

DNA double-strand break repair in parental chromatin of mouse zygotes, the first cell cycle as an origin of de novo mutation

Abstract: In the human, the contribution of the sexes to the genetic load is dissimilar. Especially for point mutations, expanded simple tandem repeats and structural chromosome mutations, the contribution of the male germline is dominant. Far less is known about the male germ cell stage(s) that are most vulnerable to mutation contraction. For the understanding of de novo mutation induction in the germline, mechanistic insight of DNA repair in the zygote is mandatory. At the onset of embryonic development, the parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 76 publications
5
109
1
4
Order By: Relevance
“…2a-e 00 ). DSBs in the spermatozoal chromosome are another form of DNA damage that influences normal embryonic development (Derijck et al 2006(Derijck et al , 2008. In this study, both karyotype analysis and immunostaining for the DSB marker, gH2AX, showed that 1 and 10 mM NaOH-treated spermatozoa had more chromosomal fragments and DSBs than those observed in fresh spermatozoa.…”
Section: Chromosome Damage In Naoh-treated Spermatozoasupporting
confidence: 51%
See 1 more Smart Citation
“…2a-e 00 ). DSBs in the spermatozoal chromosome are another form of DNA damage that influences normal embryonic development (Derijck et al 2006(Derijck et al , 2008. In this study, both karyotype analysis and immunostaining for the DSB marker, gH2AX, showed that 1 and 10 mM NaOH-treated spermatozoa had more chromosomal fragments and DSBs than those observed in fresh spermatozoa.…”
Section: Chromosome Damage In Naoh-treated Spermatozoasupporting
confidence: 51%
“…ICSI using high alkali treated spermatozoa spermatozoa, and there was no significant difference between frozen and NaOH-treated spermatozoa. Although this result suggests that NaOH treatment causes more chromosomal damage than that is observed in fresh spermatozoa, it has been reported that the DNA repair mechanism can partly rescue chromosomal damage during early embryonic development (Derijck et al 2008). …”
Section: Chromosomal Abnormalities In Embryos Injected With Naoh-treamentioning
confidence: 78%
“…However, such embryos may fail to develop to blastocysts (Fatehi et al 2006) or, if transferred to a uterus, fail to implant or, in case of implantation, result in higher miscarriage rates (Zini et al 2008;Robinson et al 2012). Even though it has been demonstrated that the oocyte and embryo retain the ability to repair DNA damage brought by the paternal genome (Ménézo et al 2010), this ability depends on the extent and type of damage (Derijck et al 2008). Of interest, a recent case report (Herrero et al 2013) demonstrated that sorting spermatozoa after magnetic elimination of apoptotic (annexin V-positive) spermatozoa from frozen semen samples of a man who had cryopreserved samples because of cancer decreased SDF and led to a successful live birth with ICSI after two previous unsuccessful attempts with unselected spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations, expanded tandem repeats and structural chromosome mutations predominate through partilineal transmission (Marchetti et al, 2007). However, sperm DNA undergoes repair in zygotes after fusion with the oocyte (Derijck et al, 2008). The zygote has several unique features influencing DNA repair depending on proteins and mRNAs of maternal origin stored in the oocyte.…”
Section: Discussionmentioning
confidence: 99%